2009
DOI: 10.1002/cm.20375
|View full text |Cite
|
Sign up to set email alerts
|

Becoming stable and strong: The interplay between vinculin exchange dynamics and adhesion strength during adhesion site maturation

Abstract: The coordinated formation and release of focal adhesions is necessary for cell attachment and migration. According to current models, these processes are caused by temporal variations in protein composition. Protein incorporation into focal adhesions is believed to be controlled by phosphorylation. Here, we tested the exchange dynamics of GFP-vinculin as marker protein of focal adhesions using the method of Fluorescence Recovery After Photobleaching. The relevance of the phosphorylation state of the protein, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 59 publications
7
68
1
Order By: Relevance
“…The strength of cellmatrix adhesions is mainly regulated through integrins whose cytoplasmic tail is linked to the actomyosin cytoskeleton through binding of focal adhesion proteins such as vinculin. In this context, vinculin has been described to act as a mechanocoupling protein (8,9,30). Here, we found that the adhesion strength of FN-coated beads is 3-fold lower in MEFvin Ϫ/Ϫ cells compared with MEFvin wt/wt cells, consistent with the notion that the mechano-coupling function of vinculin is important for firm adhesion to the ECM.…”
Section: Discussionsupporting
confidence: 88%
“…The strength of cellmatrix adhesions is mainly regulated through integrins whose cytoplasmic tail is linked to the actomyosin cytoskeleton through binding of focal adhesion proteins such as vinculin. In this context, vinculin has been described to act as a mechanocoupling protein (8,9,30). Here, we found that the adhesion strength of FN-coated beads is 3-fold lower in MEFvin Ϫ/Ϫ cells compared with MEFvin wt/wt cells, consistent with the notion that the mechano-coupling function of vinculin is important for firm adhesion to the ECM.…”
Section: Discussionsupporting
confidence: 88%
“…In the kerotinocytes, vinculin phosphorylation at Tyr 1065 was transient and was correlated with increased vinculin exchange dynamics during focal adhesion growth (39). Focal adhesion maturation was correlated with a reduction in vinculin phosphorylation and associated with an increase in cellular adhesive traction force.…”
Section: Discussionmentioning
confidence: 92%
“…The function of vinculin phosphorylation at Tyr 1065 has been previously investigated in cultured migrating human epidermal keratinocytes and a mouse embryonic fibroblast cell line using vinculin phosphorylation site mutants (39,40,50). In the kerotinocytes, vinculin phosphorylation at Tyr 1065 was transient and was correlated with increased vinculin exchange dynamics during focal adhesion growth (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Additionally, experiments on migrating keratinocytes showed a correlation between the maturation state of FAs and the amplitudes of applied forces. 13 Other studies discuss additional mechanisms for assembly and maturation of nascent adhesions. They postulate a key role of actin polymerization at adhesion sites for accumulation of α-actinin and myosin II during FA maturation.…”
Section: Introductionmentioning
confidence: 99%